Association between hTERT rs2736100 polymorphism and sensitivity to anti-cancer agents - Kim, Julie; Jones-Hall, Yava L.; Wei, Rongrong; Myers, Jamie; Qi, Yuan; Knipp, Gregory T.; Liu, Wanqing (Frontiers in Genetics, 2013)
Background: The rs2736100 single nucleotide polymorphism (SNP) is located in the intron 2 of human telomerase reverse transcriptase (hTERT) gene. Recent genome-wide association studies (GWAS) have consistently supported the strong association between this SNP and risk for multiple cancers. Given the important role of the hTERT gene and this SNP in cancer biology, we hypothesize that rs2736100 may also confer susceptibility to anti-cancer drug sensitivity. In this study we aim to investigate the correlation between the rs2736100 genotype and the responsiveness to anti-cancer agents in the NCI-60 cancer cell panel. Methods and Materials: The hTERT rs2736100 was genotyped in the NCI-60 cancer cell lines. The relative telomere length of each cell line was quantified using real-time PCR. The genotype was then correlated with publically available drug sensitivity data of two agents with telomerase-inhibition activity: Geldanamycin (HSP90 inhibitor) and RHPS4/BRACO19 (G-quadruplex stabilizer) as well as additional 110 commonly used agents with established mechanism of action. The association between rs2736100 and mutation status of TP53 gene was also tested. Results: The C allele of the SNP was significantly correlated with increased sensitivity to RHPS4/BRACO19 with an additive effect (r=-0.35, p=0.009) but not with Geldanamycin. The same allele was also significantly associated with sensitivity to antimitotic agents compared to other agents (p=0.003). The highest correlation was observed between the SNP and paclitaxel (r=-0.36, p=0.005). The telomere length was neither associated with rs2736100 nor with sensitivity to anti-cancer agents. The C allele of rs2736100 was significantly associated with increased mutation rate in TP53 gene (p=0.004). Conclusion: Our data suggested that the cancer risk allele of hTERT rs2736100 polymorphism may also affect the cancer cell response to both TERT inhibitor and anti-mitotic agents, which might be attributed to the elevated tel